2017
DOI: 10.20944/preprints201703.0102.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Promoting Sustainability Transparency in European Local Governments: An Empirical Analysis Based on Administrative Cultures

Abstract: Nowadays, the transparency of governments with respect to the sustainability of public services is a very interesting issue for stakeholders and academics. It has led to previous research and international organisations (EU, IMF, OECD, United Nations, IFAC, G-20, World Bank) to recommend promotion of the online dissemination of economic, social and environmental information. Based on previous studies about e-government and the influence of administrative cultures on governmental accountability, this paper seek… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…They concluded that the most transparent local governments are the Anglo-Saxon, followed by the Southern European and the Nordic. In addition, they confirmed the influence of administrative traditions on transparency (Navarro Galera et al, 2017).…”
Section: Ompar Ative Analysis Of Sourcesmentioning
confidence: 54%
See 1 more Smart Citation
“…They concluded that the most transparent local governments are the Anglo-Saxon, followed by the Southern European and the Nordic. In addition, they confirmed the influence of administrative traditions on transparency (Navarro Galera et al, 2017).…”
Section: Ompar Ative Analysis Of Sourcesmentioning
confidence: 54%
“…Similarly, Navarro-Galera et al (2014) studied the transparency about sustainability of 33 local governments on the websites of seven European countries, to compare Anglo-Saxon and Nordic areas. They used a questionnaire of 75 items based on the Global Reporting Initiative, about the publication of information on public-sector sustainability, incorporating economic, social and environmental vectors.…”
Section: Ompar Ative Analysis Of Sourcesmentioning
confidence: 99%
“…It is an opportunity to rethink urban environmental policies to achieve SDG 11 as society tries to recover from an unprecedented social crisis. At the same time, the observed increase in deforestation reopens academic and political debates about the role of national parks, indigenous reserves, and other categories of protection in a context of deteriorated lifestyles, illegal economies, and a lack of state presence [12,[86][87][88][89][90][91][92][93].…”
Section: Discussionmentioning
confidence: 99%
“…The attention on sustainability matters in Local Governments is one of the core themes of Agenda 21 [18] and the transparency on social, environmental and governance information in LGOs is an issue also at European level [19].…”
Section: Literature Review On the Diffusion Of Sustainability Reportmentioning
confidence: 99%
“…The literature on the sustainability reporting in LGOs is concentrated in particular on the content of SR in a single country, as introduced for example by Greco, Sciulli and D'Onza [26], or in a multicultural context [19], discussing European LGOs in sustainability disclosure and linking it with the administrative culture.…”
Section: Literature Review On the Diffusion Of Sustainability Reportmentioning
confidence: 99%